Cardio-respiratory interactions in acute asthma - Morgan Caplan; Olfa Hamzaoui; Olfa Hamzaoui (Frontiers in Physiology, 2023)
Asthma encompasses of respiratory symptoms that occur intermittently and with varying intensity accompanied by reversible expiratory airflow limitation. In acute exacerbations, it can be life-threatening due to its impact on ventilatory mechanics. Moreover, asthma has significant effects on the cardiovascular system, primarily through heart-lung interaction-based mechanisms. Dynamic hyperinflation and increased work of breathing caused by a sharp drop in pleural pressure, can affect cardiac function and cardiac output through different mechanisms. These mechanisms include an abrupt increase in venous return, elevated right ventricular afterload and interdependence between the left and right ventricle. Additionally, Pulsus paradoxus, which reflects the maximum consequences of this heart lung interaction when intrathoracic pressure swings are exaggerated, may serve as a convenient bedside tool to assess the severity of acute asthma acute exacerbation and its response to therapy.